OUTCOME OF FIXATEUR INTERNE IN THORACOLUMBAR TRAUMA - Rehman, Lal; Khattak, Azmatullah; Akbar, Ismail; Ilias, Mohammad; Nasir, Amir; Siddique, Mohammad; Mushtaq, Mushtaq (Journal of Ayub Medical College Abbottabad, 2010)
Background: Spinal cord injury (SCI) is a devastating condition often affecting young and healthy individuals around the world. This debilitating condition not only creates enormous physical and emotional cost to individuals but also is a significant financial burden to society at large. The Objective was to study the outcome of spinal fixation with fixateur interne in cases of thoracolumbar spinal injuries in terms of neurological recovery and complications. Methods: This Descriptive study was conducted at Department of Neurosurgery, Hayatabad Medical Complex and Postgraduate Medical Institute, Peshawar, from March, 2006 to December, 2007 Study included patients admitted in Neurosurgery Ward HMC, with acute traumatic spinal injuries during the above mentioned period who underwent thoracolumbar spinal fixation with fixateur interne. Name, age, sex, other relevant data, history, examination findings and investigation results were recorded. Postoperative outcome was evaluated taking neurological status, and complications like infection, implant failure and other complications into consideration. Follow-up of 6 months was carried out. Results: There were 31 patients, (18 male and 13 female). Fall from height (48%), road traffic accidents (26%) and crush injuries (26%) caused the trauma. Most common age group was from 21-30 years age. Fractured vertebrae included 2 D11 fractures, 12 D12 fractures, 13 L1 fractures, 3 L2 fractures and 1 L3 fracture. Mean operative time 80 minutes, mean blood loss 200 ml, mean hospital stay 6 days and mortality rate was 0%. Number of patients with Frankel grade A reduced from 27 to 19 and in Frankel grade E increased from 0 to 4 patients. Only one patient had infection and one patient had implant removal. Conclusion: Fixateur interne is a useful and low-cost implant for fixation of thoracolumbar junction injuries with very easy availability and easy operative insertion and little blood loss. It has excellent post-operative outcome in terms of neurological improvement and a very low complication rate. Mortality rate is minimal. Keywords: Spinal Fixation, Fixateur Interne, Thoracolumbar Injuries